Konsep Negara dalam Fiqih Siyasah - Fitriyani; Abd Basir; Abdul Rouf Fansyuri (Farabi, 2022)
The concept of the state and government is an ijtihad that reflects the exploration of rational speculative thought in order to find an intellectual basis for the function and role of the state and government as an instrumental factor for the fulfillment of the interests and welfare of the people both physically and mentally. The state, in terminology, is defined as the highest organization among a group of people who have the aspiration to unite, live in a certain area and have a sovereign government. Fiqh siyasah as one aspect of Islamic law that discusses the regulation and management of human life in the state in order to achieve the benefit of human itself regardless of the reign after the death of the Prophet Muhammad SAW. Although in the Qur'an there is not a single argument that explicitly commands or obliges Muslims to establish a state. Moreover, even the term state (Daula) is never mentioned in the Qur'an, however, the basic elements in society, nation and state, can be found in it. Some of the main principles include: Deliberation, Justice, Equality.